Cloud ice fraction governs lightning rate at a global scale - Yong Han (Nature Portfolio, 2021)
Lightning rate varies non-linearly with cloud ice fraction and between ocean and continent regions due to differences in convection depth, according to analyses of 20-years of lightning observations and cloud water data.